The clinical and pathological histology efficacy of biological therapy for severe asthma with a phenotype of type 2 inflammation - systematic review - Ma, Junhui; Ma, Qiang; Yang, Jing; Liang, Panpan; Zhou, Jiaxin; Ma, Jiarui; Ma, Fuhua; Zhuan, Bing; Zhou, Wei (Frontiers in Immunology, 2025)
Asthma is a complex, chronic inflammatory condition of the airways that comes in many forms. Because different inflammatory processes drive it, we can generally categorize asthma into two main types: type 2 inflammatory asthma and non-type 2 inflammatory asthma. Type 2 inflammation is usually the culprit in most folks grappling with severe asthma. There is a noticeable difference in the treatment approaches for different phenotypes of severe asthma. The main reason is that patients suffering from type 2 inflammatory asthma can respond well to treatment with biological agents. Several well-verified biological agents, such as anti-immunoglobulin E (IgE) monoclonal antibodies, anti-interleukin (IL)-4 monoclonal antibodies, anti-IL-5 monoclonal antibodies, and anti-thymic stromal lymphopoietin (TSLP) monoclonal antibodies, have shown outstanding effectiveness. They can significantly alleviate asthma exacerbations, lower the number of eosinophils, improve pulmonary function, decrease the dependence on oral corticosteroids, and elevate the quality of life for patients with asthma. This discourse meticulously evaluates the therapeutic prowess of biological agents in the treatment and control of severe asthma, concurrently investigating their impact on histological indices, to highlight the crucial role of precision medicine in the strategic concatenation of therapy for this refractory malady.